2007
DOI: 10.21236/ada474475
|View full text |Cite
|
Sign up to set email alerts
|

On the Viability of Magnetometer-Based Projectile Orientation Measurements

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to Department of Defense, Washington Headquarters Services, Directorate for Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Thus, at each time step, the signals are first normalized using running estimates of bias and scale factor for each signal obtained from peak detection, yielding normalized outputs M J and M K . Harkins [36] has shown that these normalized outputs are the sine and cosine, respectively, of the roll angle offset by a phase angle determined by the magnetic field vector and projectile Euler angles, given by for the J B and K B magnetometers, respectively. Equations (22) and (23) show that for a given magnetometer signal, two roll angles are equally likely.…”
Section: A Sensor and Dynamic Modelsmentioning
confidence: 99%
“…Thus, at each time step, the signals are first normalized using running estimates of bias and scale factor for each signal obtained from peak detection, yielding normalized outputs M J and M K . Harkins [36] has shown that these normalized outputs are the sine and cosine, respectively, of the roll angle offset by a phase angle determined by the magnetic field vector and projectile Euler angles, given by for the J B and K B magnetometers, respectively. Equations (22) and (23) show that for a given magnetometer signal, two roll angles are equally likely.…”
Section: A Sensor and Dynamic Modelsmentioning
confidence: 99%
“…Therefore, great effort has been taken to measure it. The existing test method on projectile's attitude mainly consists of high speed photography, [4][5][6][7][8][9][10] onboard instrumentation, [10][11][12][13] and the optical level principle. [14][15][16][17][18][19][20][21][22][23][24][25] Due to the obscurity caused by the gun barrel, high speed photography is unable to measure the projectile's movement in the bore.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 8 ], Harkins et al reported that the magnetic roll rate and projectile spin rate were equal only when there was no yaw motion or the spin axis was perpendicular to the local field vector. In [ 9 ], Harkins et al explained that when the spin rate was high with respect to the yaw rate, the projection of the local field vector onto the projectile’s radial axis varies with the spin rate. In [ 10 ], Harkins et al also pointed out that when the spin rate was high with respect to the yaw rate and pitch rate, the projectile spin rate estimated by roll period method was more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…In the time domain analysis method, the signal period will be estimated to track the signal frequency. The period measurement method used commonly includes peak detection [ 6 , 8 , 9 , 10 , 11 , 12 , 13 ] and zero crossing detection [ 6 , 10 , 14 , 15 , 16 ]. In spite of the relatively bigger error, lower sampling rate and the need for sparse data interpolation, time domain analysis method has been widely used in the field of navigation and guidance due to its instantaneity.…”
Section: Introductionmentioning
confidence: 99%